Health service engagement with consumers and community in Australia for issue: Engagement and accountability with your community. Issue 4 (21st November 2019) - Rendalls, Shane; Spigelman, Allan D.; Goodwin, Catherine; Daniel, Nataliya
Abstract : Purpose: The purpose of this paper is to provide an overview of consumer and community engagement in health service planning, quality improvement and programme evaluation in Australia, and key components and importance of a strong suite of tools for achieving effective outcomes. Design/methodology/approach: This paper is a non-systematic review of Australian national, state and territory websites in relation to policy commitment to consumer engagement, best practice framework for consumer engagement and recent project example. Findings: Consumer engagement is a recognised component of the Australian health system. It is reflected in the national and state health policy and is a mandatory requirement of hospital accreditation. The application of co-design principles is gaining increasing popularity in health service planning and programme evaluation. Co-design is an important enabler of patient/community-centred service planning and evaluation; however, on its own it may lead to poorer outcomes. Co-design must occur within a broader systemic framework. Practical implications: The research identifies a conceptual framework, approaches and tools of value to health service management and planners. Originality/value: Consumer and community engagements are critical to the development of consumer-centric services. However, this should complement and add value to, not divert attention away from established principles of service planning, continuous quality improvement and programme evaluation. To do so may result in poorer quality health and well-being outcomes, reduced efficiency and ultimately reduced consumer and community satisfaction with services. This paper examines consumer and community engagement within the broader planning and quality improvement framework and practical implications for keeping planning, research and evaluation on track.